Methodology for reporting Interactions between product and production system in the early phases of product development - a practical example - Petersen, Marcus; Bandak, Shatha; Gausemeier, Jürgen; Iwanek, Peter; Schneider, Marcel
Innovative products are based on an interdisciplinary interaction between mechanics, electronics and information technology. The close interplay of the specialist disciplines makes special demands on the development process. For example, a uniform understanding of the specialists is particularly important for an efficient development of the product and the associated production system. Furthermore, the product concept often already determines the production system, even though new production technologies make innovative products possible in the first place. Therefore, the interactions between the product and the production system must be taken into account from the start during development. Currently, the development is mostly carried out separately in the specialist disciplines on the basis of existing methods and systematics, who often do not fully consider the existing interactions. Time-consuming and costly iteration loops are the result. This article therefore addresses the interactions and mutual dependencies between the product and the production system in the early phases of product development, such as an adaptation of the product design due to assembly requirements. The development process of a flashlight serves as an example. First, the interactions are described and analyzed. A methodology is then presented that takes these interactions into account in the context of the integrative development of product and production system in the early phases of product development. The methodology consists of a process model, a specification technique and a software tool. The process model serves as a guideline for the integrative development of product and production system, whereas the specification technology forms the core of the methodology and enables interdisciplinary collaboration of all people involved. For the product concept, the specification technology encompasses the aspects of the environment, application scenarios, requirements, functions, effective structure, behavior and design. The principle solution of the production system is represented by the aspects of production requirements, process sequence, resources and design. The software tool supports the developer in applying the methodology. The methodology presented is then demonstrated using the example product. whereas the specification technology forms the core of the methodology and enables interdisciplinary collaboration of all people involved. For the product concept, the specification technology encompasses the aspects of the environment, application scenarios, requirements, functions, effective structure, behavior and design. The principle solution of the production system is represented by the aspects of production requirements, process sequence, resources and design. The software tool supports the developer in applying the methodology. The methodology presented is then demonstrated using the example product. whereas the specification technology forms the core of the methodology and enables interdisciplinary collaboration of all people involved. For the product concept, the specification technology encompasses the aspects of the environment, application scenarios, requirements, functions, effective structure, behavior and design. The principle solution of the production system is represented by the aspects of production requirements, process sequence, resources and design. The software tool supports the developer in applying the methodology. The methodology presented is then demonstrated using the example product. Active structure, behavior and shape. The principle solution of the production system is represented by the aspects of production requirements, process sequence, resources and design. The software tool supports the developer in applying the methodology. The methodology presented is then demonstrated using the example product. Active structure, behavior and shape. The principle solution of the production system is represented by the aspects of production requirements, process sequence, resources and design. The software tool supports the developer in applying the methodology. The methodology presented is then demonstrated using the example product.